Landasan Filosofis dan Corak Pendekatan Abdurrahman Wahid Tentang Implementasi Hukum Islam di Indonesia - Athoillah Islamy (Al-Adalah: Jurnal Hukum dan Politik Islam, 2021)
This study aims to explore and identify the philosophical basis and features of Abdurrahman Wahid's approach to Islamic law regarding the implementation model of Islamic law in Indonesia. This research is a qualitative research in the form of literature review. This research is included in the category of philosophical normative Islamic law research. The theory used as a theory of analysis is the theory of the formalization paradigm of Islamic law. There are two major conclusions in this study. First. First, the indigenousization of Islam is Abdurrahman Wahid’s philosophical foundation for the implementation model of Islamic law through the method of contextual interpretation and contextualization of classical Islamic law. Second, Abdurrahman Wahid’s approach related to the implementation of Islamic law in the context of people's life in Indonesia is a cultural substantive approach